Immortal demon slayer [videorecording (DVD)] - Peng, Yuyan, 1982-; Ni, Ni, 1988-; Yu, Wenle, 1981- (Crimson Forest Films, 2018)
Five hundred years before the Monkey King wreaks havoc on the heavenly kingdom, Wukong refuses to bow down to his destiny when he sets out to rebel against the gods.